2017
DOI: 10.1016/j.cbpa.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin system in pejerrey fish (Odontesthes bonariensis). Characterization and gene expression pattern during early developmental stages

Abstract: In vertebrates, kisspeptins and their receptors are known to be related to puberty onset and gonadal maturation, however, there are few studies concerning their role in early development. Here, we characterize the kisspeptin system in the pejerrey, Odontesthes bonariensis, a fish with strong temperature-dependent sex determination. We reconstructed the phylogenetic history of the two ligands (kiss1 and kiss 2) and two receptors (kissr2 and kissr3) in pejerrey in the context of recent classifications of bony fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 71 publications
2
23
0
1
Order By: Relevance
“…In some species, both kisspeptins are detected in the gonads [medaka and zebrafish ( 42 , 53 ); sea bass ( 60 ); rohu ( 45 ); and Catla catla ( 46 , 47 )]. In contrast, in the chub mackerel, Kiss1 is expressed in the gonads of both sexes, while Kiss2 expression is not detected ( 44 ), whereas in the pejerrey, expression of both genes is very low in the gonads ( 48 ). We previously showed a strong expression of KissR-1 in both the ovary and testis of the European eel ( 19 ), which supports a potential endocrine action of Kiss1 and/or Kiss2 on European eel gonads.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In some species, both kisspeptins are detected in the gonads [medaka and zebrafish ( 42 , 53 ); sea bass ( 60 ); rohu ( 45 ); and Catla catla ( 46 , 47 )]. In contrast, in the chub mackerel, Kiss1 is expressed in the gonads of both sexes, while Kiss2 expression is not detected ( 44 ), whereas in the pejerrey, expression of both genes is very low in the gonads ( 48 ). We previously showed a strong expression of KissR-1 in both the ovary and testis of the European eel ( 19 ), which supports a potential endocrine action of Kiss1 and/or Kiss2 on European eel gonads.…”
Section: Discussionmentioning
confidence: 86%
“…In other teleosts presenting two Kiss genes, both Kiss1 and Kiss2 mRNAs are also expressed in the central nervous system [RT-PCR and qPCR, zebrafish ( 40 42 ); RT-PCR, goldfish ( 43 ); RT-PCR, sea bass ( Dicentrarchus labrax ), medaka ( Oryzias latipes ) ( 42 ); RT-PCR and qPCR, chub mackerel ( 44 ); qPCR, rohu, Labeo rohita ( 45 ); qPCR, Catla catla ( 46 , 47 ); qPCR, pejerrey, Odontesthes bonariensis ( 48 )], suggesting that kisspeptins exert important functions in the teleost brain. Anatomical studies, using ISH and laser-capture microdissection coupled with qPCR, have demonstrated that each transcript is located in different brain nuclei: Kiss1 mRNA is observed in the ventral habenula , while Kiss2 mRNA is found in the preoptic region and in the hypothalamus [for review see Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, a diferencia de lo documentado para mamíferos, los peces tienen dos genes Kiss (kiss1 y kiss2) debido a duplicaciones del genoma (Mechaly et al, 2013;Ohga et al, 2018). Sin embargo, a pesar de que los niveles de kisspeptina1 y 2 varían durante el ciclo sexual (Tovar Bohórquez et al, 2017), la relación entre kisspeptina y reproducción en peces no parece ser tan directa como en tetrápodos (Tang et al, 2015;Nakajo et al, 2018).…”
Section: Morfología De La Aleta Anal Y Modelo Para Definir Sus Estadiosunclassified